ANALISIS NILAI MORAL DALAM NOVEL AYAT-AYAT CINTA 2 KARYA HABBIBURAHMAN EL SHIRAZY - Sartika, Sartika; Martono, Martono; Priyadi, Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractMoral is an act or action carried out in accordance with accepted ideas or public opinions which include social unity in certain environments. This research is motivated by the author of the novel Ayat-ayat Cinta 2 by habbiburahman El Shirazy who is very brave in expressing the polemic between religion and politics that is being experienced by the world today. The purpose of this study is to know individual moral values with God, individual moral values with society, and the implementation of literary learning in schools. The research instrument is documentation. Research data are phrases, sentences, and quotes, which are related to research. Data analysis techniques are observation, triangulation and referential. The results of the study show that there are 9 individual moral values with God and individual moral values with society 4. The results of this study are integrated with Indonesian language learning in class XII high school equivalent to the 2013 curriculum with KD 3.3 analyzing novel texts both oral and written and KD 4.3 produces new texts coherent according to the characteristics of the text both oral and written.. Keywords: analysis, moral values, Ayat-ayat Cinta 2